Pengaruh Stres Kerja, Gaya Kepemimpinan, Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada Karyawan di Kantor PDAM Kabupaten Grobogan) - Rifa'i, Haris, Sri Murwanti, S.E., M.M (2015)
This research has a purpose to find out how to effect of job stress, leadership style, motivation and work environment on the performance of employees at the district office PDAM Grobogan. This research subject is employees at the district office PDAM Grobogan as many as 84 respondents. with the data collection method that uses observation and questionnaires. By using the construct validity and reliability as a means of testing instruments, classic assumption test, multiple linear regression analysis, hypothesis testing partially (t-test) and simultaneous (f-test) and the coefficient of determination (R^2)is used to obtain the results accurate data in order to draw conclusions. Then the results showed that job stress will negatively affect the performance of employees, while leadership style, motivation and work environment positively effect on the performance of employees. And it can be concluded that job stress, leadership style, motivation and work environment really significantly affect the performance of employees at the District PDAM Grobogan. Key words: employee performance, Job Stress, Leadership Style, Motivation and Work Environment